Evapotranspiration and assessment of water consumed in irrigated area of the Brazilian Semiarid Region by remote sensing - Silva, Bernardo Barbosa da; Braga, Alexandra Chaves; Braga, Célia Campos; Oliveira, Leidjane Maria Maciel de; Galvíncio, Josiclêda Domiciano; Montenegro, Suzana Maria Gico Lima (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to map the actual evapotranspiration (ETr) and to determine the volume of water used in the irrigation project of São Gonçalo, PB, in the Brazilian Semiarid Region, using remote sensing. TM/Landsat 5 images were acquired from the study area, in 2008, and were used to obtain thematic maps of daily ETr. Two dwarf coconut crops were selected for validation of the results of evapotranspiration obtained by the surface energy balance algorithm for land (ETSebal) and the FAO‑56 method (ETFAO). In order to determine ETFAO, the product between the culture coefficient, the adjustment coefficient, and the reference evapotranspiration was used. The differences obtained by the two techniques resulted in root mean square error, mean relative error, and mean absolute error equal to 0.53 mm, 9.46%, and 0.43 mm, respectively. In the irrigated areas, ETr represented about 85% of net radiation and, in rainfed plots, only 12.5%. The mapping of ETr clearly delimitated the irrigated and nonirrigated plots, as well as the differences within the irrigated perimeter of the project under investigation. The volume of water applied in the irrigation project, only in the period from July to December, represents more than 60% of the capacity of the São Gonçalo reservoir.